The Principle of Balances in Prenuptial Agreements to Protect the Rights of Future Spouses - Yosephine, Yolanda; Ramadhani, Dwi Aryanti (International Journal of Science and Society, 2024)
The prenuptial agreement is regulated under Article 29 of Law Number 1 of 1974. This agreement is made either during or before the marriage takes place. The prenuptial agreement must be made and legalized in the presence of a lawyer or notary, and then ratified by the Religious Affairs Office (KUA) or Civil Registration Office. The research method used in this study is a normative juridical approach, focusing on issues within the scope of prenuptial agreement. The principle of balance is crucial to emphasize in order to ensure equality between the rights and obligations of the parties involved. A prenuptial agreement typically includes main clauses concerning property division, rights and obligations, child protection, and dispute resolution. The Indonesia government need to provide education to the public about the principle of balance in prenuptial agreements. The government should also establish standard clauses that accurately reflect this principle of balance, and should cover all important matters typically included in such agreements.